Growth in utero and serum cholesterol concentrations in adult life. Issue 6918 (11th December 1993) - Barker, D J; Martyn, C N; Osmond, C; Hales, C N; Fall, C H
Abstract : OBJECTIVE--To see whether reduced rates of fetal growth are related to raised serum cholesterol concentrations in adult life. DESIGN--Follow up study of men and women whose size at birth had been recorded. SETTING--Jessop and Northern General Hospitals, Sheffield. SUBJECTS--219 men and women born in the Jessop Hospital during 1939-40. MAIN OUTCOME MEASURES--Serum concentrations of total cholesterol, low density lipoprotein cholesterol, and apolipoprotein B. RESULTS--Men and women who had had a small abdominal circumference at birth had raised serum concentrations of total and low density lipoprotein cholesterol and apolipoprotein B. This was independent of the duration of gestation. Serum concentrations of total cholesterol fell by 0.25 mmol/l (95% confidence interval 0.09 to 0.42) with each 1 in (2.54 cm) increase in abdominal circumference. The corresponding figure for serum low density lipoprotein cholesterol was 0.26 mmol/l (0.11 to 0.42) and for serum apolipoprotein B 0.04 g/l (0.02 to 0.07). Small head and chest circumferences at birth and short length were each associated with raised serum low density lipoprotein cholesterol concentrations but the trends disappeared in a simultaneous regression with abdominal circumference at birth. The association between abdominal circumference at birth and low density lipoprotein cholesterol concentration was independent of social class, current body weight, cigarette smoking, and alcohol consumption. CONCLUSION--Raised serum cholesterol concentrations in adult life are associated with impaired growth during late gestation, when fetal undernutrition has a disproportionate effect on liver growth. Impaired liver growth may permanently alter low density lipoprotein cholesterol metabolism.